Fulfilling the Call to Holiness in the Views of Cardinal Stefan Wyszyński. An Outline of the Problem in the Light of the Ascetic Teachings of the Servant of God - Hadryś, Jacek (Verbum Vitae, 2021)
The article outlines the issue of fulfilling the call to holiness based on the hitherto little-known ascetic teachings of Stefan Cardinal Wyszyński. All the research work was carried out by analyzing Wyszyński’s statements about the universal call to holiness and its four dimensions: theological, moral, ecclesial and psychological. The results of the analysis of the source texts were assessed in the light of the exhortation Gaudete et exsultate by Pope Francis. It was found that Wyszyński’s teachings on the realization of the call to holiness lost nothing of its topicality and is fully rooted in the tradition of the Church.